Day 2 Thu, February 16, 2017 2017
DOI: 10.2118/185001-ms
|View full text |Cite
|
Sign up to set email alerts
|

Steam-Solvent Coinjection under Reservoir Heterogeneity: Should ES-SAGD be Implemented for Highly Heterogeneous Reservoirs?

Abstract: Expanding-solvent steam-assisted gravity drainage (ES-SAGD) is a widely-investigated alternative to SAGD, considering its potential to reduce thermal losses while enhancing bitumen recovery. However, most prior studies on ES-SAGD were limited to homogeneous reservoirs. This research presents a mechanistic analysis of ES-SAGD in heterogeneous reservoirs in terms of cumulative steam-oil ratio (SOR) as a function of steam-chamber size. Simulation case studies for SAGD and ES-SAGD with normal hexane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The feasibility of adding solvent into steam has also been validated. Based on these studies, the suitable reservoir condition was investigated [14,15], and the impact of shale barriers on SAGD performance and the hybrid optimization techniques were used to design the solvent-assisted SAGD process [16,17]. Although exponentially reducing the oil viscosity, the solvent is less effective in diffusing into shale barriers and speeds up the steam chamber evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of adding solvent into steam has also been validated. Based on these studies, the suitable reservoir condition was investigated [14,15], and the impact of shale barriers on SAGD performance and the hybrid optimization techniques were used to design the solvent-assisted SAGD process [16,17]. Although exponentially reducing the oil viscosity, the solvent is less effective in diffusing into shale barriers and speeds up the steam chamber evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been done to demonstrate the impact of shale barriers on SAGD performance. Kumar and Hassanzadeh have presented a detailed literature review on the impact of shale barriers on SAGD and ES-SAGD . However, very few studies are available regarding the impact of shales on ES-SAGD performance. A major industry standard to assess the performance of SAGD and ES-SAGD is the steam oil ratio (SOR). The conventional range of the SOR for an efficient SAGD process in a homogeneous reservoir tends to fall between 2 and 3.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional range of the SOR for an efficient SAGD process in a homogeneous reservoir tends to fall between 2 and 3. Studies based on ES-SAGD performance evaluation in the presence of shale barriers were based on the use of heptane and hexane as solvents. , All the studies reported an improved performance by ES-SAGD over SAGD in the presence of shale barriers. This paper proposes a further detailed study on comparing SAGD and ES-SAGD in heterogeneous reservoirs over a wide range of shale densities.…”
Section: Introductionmentioning
confidence: 99%